Press and Social Development - saman khodayari; abbas asadi (توسعه اجتماعی)
Our concerns about the world have less to do with what is really happening than with what the journalists and media tell us about them. The present study mainly aims at recognizing the performance of Iranian press and its developmental role, especially its role in social development. To this aim, content analysis was used as the methodology of the study and two newspapers with two different political agendas were selected. Then, based on classified sampling method, fourty eight issues of the two newspapers were selected and analysed according to the coding instructions. As per the findings of this study on the basis of the Chi-square test, there is no meaningful relationship between the two variables of the newspapers and their content; there is also no meaningful relationship between the two variables of the analysed newspapers and the presentation of constructive suggestions and usefulness of their criticisms. According to the results, the most frequent topic in the social development debate in the two newspapers was education/literacy, with immigration having the lowest share. It was also found that the content including constructive criticism and useful suggestions are less abundant than those including criticism, and it was finally revealed that in the two newspapers, few work has been done in pursuit of the officials' promises and the results of the social plans passed for eliminating the existing social harms.